2018
DOI: 10.1177/0022429418806304
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pre-Tuning Vocalization Behaviors on the Tuning Accuracy of College Instrumentalists

Abstract: The purpose of this study was to examine the effects of two pre-tuning vocalization behaviors (humming and singing) on the tuning accuracy of woodwind and brass instrumentalists. Undergraduate collegiate musicians ( N = 72) performed a sustained stimulus pitch (concert B-flat) while engaging in one of the two conditions or the control condition (silence). We also explored the relationships between participants’ tuning accuracy and their tuning confidence, examined the reasons instrumentalists provided for thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 28 publications
(53 reference statements)
2
13
0
3
Order By: Relevance
“…Interestingly, 21 participants (37.5%) played most in tune in the neutral instruction condition, but the other 35 (62.5%) participants actually played more in tune in other conditions. Consistent with previous research indicating weak relationships between musicians’ pitch perception and production (Ely, 1992; Morrison, 2000; Schlegel & Springer, 2018; Silvey et al, 2019), it seems that our participants’ perceived most accurate performance did not match their actual most accurate performance. It is also possible that our participants believed that they should play with their best tone in the neutral condition, which could suggest that their default behavior is their best sound.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Interestingly, 21 participants (37.5%) played most in tune in the neutral instruction condition, but the other 35 (62.5%) participants actually played more in tune in other conditions. Consistent with previous research indicating weak relationships between musicians’ pitch perception and production (Ely, 1992; Morrison, 2000; Schlegel & Springer, 2018; Silvey et al, 2019), it seems that our participants’ perceived most accurate performance did not match their actual most accurate performance. It is also possible that our participants believed that they should play with their best tone in the neutral condition, which could suggest that their default behavior is their best sound.…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, Ely (1992) indicated that timbre affected participants’ judgments of tone pairs even though timbre did not influence their tuning accuracy on a performance task. Not surprisingly, weak relationships were found between perceived intonation accuracy and actual intonation accuracy in previous studies (Schlegel & Springer, 2018; Silvey et al, 2019).…”
Section: Pitch–timbre Interactionsmentioning
confidence: 62%
See 2 more Smart Citations
“…Previous research has demonstrated mixed results concerning the effects of vocalization (e.g., singing) on intonation, with some results indicating that it provided positive effects on pitch discrimination (e.g., Elliott, 1974; Jones, 2003) and others indicating that it had no effect on pitch matching (e.g., Bennett, 1994; South, 2013). Silvey et al (2019) tested for the effects of two types of vocalization—singing and humming—on wind instrumentalists’ tuning accuracy while performing concert B-flat tuning notes. Participants completed a tuning task three times.…”
Section: Vocalizationmentioning
confidence: 99%